A study of the growth process of Co3O4 microcrystals synthesized via a hydrothermal method. Issue 2 (12th January 2016) - Hongyan, Xu; Jiangtao, Diwu; Zhenyin, Hai; Libo, Gao; Qiang, Zhang; Jun, Tang; Binzhen, Zhang; Chenyang, Xue
Abstract : Co3 O4 microcrystals are synthesized by hydrothermal method. As the thermal‐treatment time increases from 2 h to 24 h, the microcrystal shape changes from hedgehog sphere‐like to lamellar, cubic‐like and finally perfect cubic. Then, more hydrothermal treatment time only leads to the growth and aggregation of Co3 O4 grains. The cubic Co3 O4 microcrystals in uniform size (∼6 μm) are synthesized via a 12‐h thermal treatment.2 Abstract : Pure Co3 O4 microcrystals were prepared by a hydrothermal method from Co(NO3 )2 ·6H2 O and urea solution, and the effect of thermal treatment time on the growth of Co3 O4 microcrystals was studied by X‐ray diffraction (XRD), scanning electron microscopy (SEM), Raman and UV‐Vis absorption spectra. The results show that with the thermal treatment time increases from 2 h to 12 h, the shape of as‐prepared Co3 O4 microcrystals changes from the hedgehog sphere‐like to the as‐cubic one that were stacked by lots of lamella, and finally cubes, and then longer time treatment will only lead to the size growth and agglomeration of particles. In conclusion, the cubic Co3 O4 microcrystals of uniform size (∼6 μm) are synthesized via a 12‐h thermal treatment. Moreover, the synthesis mechanism has been studied.